Waqf as an Instrument for Social Security System: A Framework for Society’s Welfare - Hafas Furqani; Muhammad Arifin; Khairudin; Ratna Mulyany (Badan Wakaf Indonesia, 2025)
Abstract: Waqf, an enduring institution in Islamic economic thought, holdssignificant potential as an instrument for ensuring society’s welfare through asustainable social security system. This paper proposes a conceptual frameworkthat integrates waqf into contemporary social protection mechanisms, aiming toaddress poverty alleviation, income inequality, and community empowerment.Drawing from classical jurisprudence and modern institutional models, theframework outlines governance structures, operational mechanisms, and financingstrategies that align with the principles of transparency, accountability, andmaqāṣid al-sharīʿah (objectives of Islamic law). The study highlights the role ofwaqf assets in providing long-term funding for essential services such ashealthcare, education, housing, and livelihood support. It also examines thesynergy between waqf-based initiatives and governmental welfare programs toenhance resilience and reduce dependency on short-term aid. The proposed modeloffers a strategic pathway for policymakers, waqf managers, and social welfareinstitutions to revitalize waqf as a viable, equitable, and sustainable pillar of socialsecurity in the modern era.Keywords: waqf, social security, society’s welfare, Islamic economics, sustainabledevelopment